Meta Principalism: Simple Guiding Concept for Self Preparation of Private School Principal of Nepal - Pokharel, Babin (Journal of Education and Vocational Research, 2015)
A school leader of the today’s world possesses a vast array and network of skills. The 21st century principal has knowledge of and appreciation for the educational system, has a strong foundation and diverse repertoire of skills and strategies, which are theoretically based, and develops and maintains trusting, positive and supportive relationships. In order to be a changed principal required by 21st century, all of these traits, skills, behaviors and situational factors need to be attached together, in order to understand and appreciate the big picture in terms of viewing the principal as an educational leader and change agent. Simple guiding principal of Meta principalism gives a clear concept of principalism required for 21 st century. I found out that school principal makes a difference in school and student performance if they are granted the autonomy to lead in more transformative way. Their skills and knowledge for different leadership styles, teamwork, and monitoring, of instructional and administrative functions makes them qualified to perform par excellence in leading private school of Nepal. Hence, Meta principalism brings leadership preparation and training into new meanings which are central force of private schools of Nepal to stimulate and spread innovation and to develop effective and self prepared principal that can bring substantial benefits to both schools and community.